2020
DOI: 10.1136/bmjnph-2020-000107
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk of obesity as a modifier of associations between neighbourhood environment and body mass index: an observational study of 335 046 UK Biobank participants

Abstract: BackgroundThere is growing recognition that recent global increases in obesity are the product of a complex interplay between genetic and environmental factors. However, in gene-environment studies of obesity, ‘environment’ usually refers to individual behavioural factors that influence energy balance, whereas more upstream environmental factors are overlooked. We examined gene-environment interactions between genetic risk of obesity and two neighbourhood characteristics likely to be associated with obesity (p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…Reduced prices of low-energy dense foods may provide motivation to purchase and subsequently consume these foods, which may be intrinsically less appealing to individuals with higher polygenic risk for obesity. A recent study reported an interaction between genetic risk to obesity and proximity to fast-food outlets on BMI [13]. Although the food environment was evaluated with a different measure, the result adds support to our findings of a moderating effect of the food environment on genetic susceptibility to obesity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Reduced prices of low-energy dense foods may provide motivation to purchase and subsequently consume these foods, which may be intrinsically less appealing to individuals with higher polygenic risk for obesity. A recent study reported an interaction between genetic risk to obesity and proximity to fast-food outlets on BMI [13]. Although the food environment was evaluated with a different measure, the result adds support to our findings of a moderating effect of the food environment on genetic susceptibility to obesity.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, previous studies have reported that adherence to healthy dietary patterns and limiting consumption of sugar sweetened beverages and fried food might attenuate the genetic risk associated with elevated BMI [10][11][12]. One recent study reported a significant interaction between genetic risk to obesity and proximity to fast-food outlets on BMI [13]; however, no study has evaluated the interactions between everyday exposures to food cues in the in-store retail food environment and genetic susceptibility to obesity on diet and anthropometric outcomes. Some of the variants implicated in genetic risk for obesity are involved in neurobehavioral circuits related to dopamine reward and food cue responsivity, suggesting that exposures to in-store retailer food cue stimuli may affect ingestive behavior in distinct ways according to genetic background.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have typically only tested the additive scale for interaction. 15,16,19,30 Because effect modification can occur on either the additive scale or the multiplicative scale, we analysed both scales. 18,19 Relevance for public health…”
Section: Results In Contextmentioning
confidence: 99%
“…14 PGSs have previously been employed to assess gene*environment interactions or effect modifications for cardiovascular traits, including for educational achievement, neighbourhood and obesogenic environments. [15][16][17] Identifying these effects may help to understand the relationship between early life environmental exposures and CVD risk in adult life.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, however, gene-environment interactions have been seen in humans [67][68][69][70][71][72] , but there has been controversy around which environmental factors play a role. In fact, Tyrell et al 73 recently identified multiple environmental factors that interacted with obesogenic alleles to affect susceptibility to obesity in humans, but, similar to our findings, "Western" diet was not found to be a significant factor, bringing into question these earlier findings 73 .…”
Section: Discussionmentioning
confidence: 99%